Modified technique to increase nostril cross-sectional area after using rib and septal cartilage graft over alar nasal cartilages - Wulkan,Marcelo (2012)
PURPOSE: Describe a modified technique to increase nostril cross-sectional area using rib and septal cartilage graft over alar nasal cartilages. METHODS: A modified surgical technique was used to obtain, carve and insert cartilage grafts over alar nasal cartilages. This study used standardized pictures and measured 90 cadaveric nostril cross-sectional area using Autocad®; 30 were taken before any procedure and 60 were taken after grafts over lateral crura (30 using costal cartilage and 30 using septal cartilage). Statistical analysis were assessed using a model for repeated measures and ANOVA (Analysis of Variance) for the variable "area". RESULTS: There's statistical evidence that rib cartilage graft is more effective than septal cartilage graft. The mean area after the insertion of septal cartilage graft is smaller than the mean area under rib graft treatment (no confidence interval for mean difference contains the zero value and all P-values are below the significance level of 5%). CONCLUSIONS: The technique presented is applicable to increase nostril cross section area in cadavers. This modified technique revealed to enhance more nostril cross section area with costal cartilage graft over lateral crura rather than by septal graft.